90 days to success as a small business owner - Thomsen, Barry (Boston MA Course Technology, 2012)
Most small-business owners spend the majority of their time running their business rather than growing it. Although successful businesses may begin with a great idea, they need more than that to grow and prosper; they need an action plan for success. 90 DAYS TO SUCCESS AS A SMALL BUSINESS OWNER provides that plan. This book contains hundreds of strategies that small-business owners can introduce into their daily routine to keep valued customers and attract new ones. Topics range from product positioning, pricing, and advertising to employee management, customer service, and brand loyalty. With an emphasis on proven methods and concrete action items, the book also includes quick reference checklists and self-assessments that make it a must-have field guide for the small-business owner who is preparing for startup or ready to grow an existing business.
Includes index.
Keywords: Small business--Management.